An in-depth study of the policies implemented by the Housing & Development Board to curb speculative demand. - Ho, Lionel Tun Siong. (2008)
The heating up of public housing market by speculators had indeed caused a stir among the public. Prices have skyrocketed and demand for new flats has increased. As such, the queue for new flats lengthened quite a bit. Our aim in this project is to analyse the effects of the many policies which the Housing & Development Board (HDB) implemented to control the heating up of the market. This study is important also because about 87% of the Singapore population is housed in HDB flats.